Cell cycle arrest and apoptotic studies of Terminalia chebula against MCF-7 breast cancer cell line: an in vitro and in silico approach - Reddy, Pruthvish; Pradeep, Sushma; S. M., Gopinath; Dharmashekar, Chandan; G., Disha; M. R., Sai Chakith; Srinivasa, Chandrashekar; Shati, Ali A.; Alfaifi, Mohammad Y.; Elbehairi, Serag Eldin I.; Achar, Raghu Ram; Silina, Ekaterina; et al. (Frontiers in Oncology, 2023)
Breast cancer is a leading cause of mortality in women, and alternative therapies with fewer side effects are actively being explored. Breast cancer is a significant global health concern, and conventional treatments like radiotherapy and chemotherapy often have side effects. Medicinal plant extracts offer a promising avenue for the development of effective and safe anticancer therapies. Terminalia chebula, a plant known for its medicinal properties, was selected for investigation in this study. We aimed to assess the antiproliferative effects of TCF extract on breast cancer cells and explore the potential role of saccharopine, a phytochemical found in TCF, as an anticancer agent. MCF7 breast cancer cell lines were exposed to TCF extract, and cell viability and apoptosis assays were performed to evaluate the antiproliferative and apoptogenic effects. Molecular docking studies were conducted to assess the binding affinity of saccharopine with EGFRs. Molecular dynamics simulations and binding energy calculations were employed to analyze the stability of the EGFR-saccharopine complex. The TCF extract exhibited significant antiproliferative effects on MCF7 breast cancer cells and induced apoptosis in a dose-dependent manner. Molecular docking analysis revealed that saccharopine demonstrated a higher binding affinity with EGFR compared to the reference compound (17b-estradiol). The subsequent MDS simulations indicated stable binding patterns and conformation of the EGFR-saccharopine complex, suggesting a potential role in inhibiting EGFR-mediated signaling pathways. The investigation of Terminalia chebula fruit extract and its phytochemical saccharopine has revealed promising antiproliferative effects and a strong binding affinity with EGFR. These findings provide a foundation for future research aimed at isolating saccharopine and conducting in vivo studies to evaluate its potential as a targeted therapy for breast cancer. The development of novel anticancer agents from plant sources holds great promise in advancing the field of oncology and improving treatment outcomes for breast cancer patients.